Uji Usability Staffing Database Application Based on YII Framework - Mohammad Syahidul Haq; Nur Aini Dwi Setyowati; Najlatun Naqiyah (Universitas Negeri Malang, 2022)
Abstract: The development of information systems and technology plays an important role in improving the quality of management activities, one of which is the management of personnel data. One thing that comes to mind when talking about something that can be used to store, process and provide personnel data is a personal data management system. The personal data management system was developed to make it easy for users to collect and manage their data digitally. The Yii Framework-based Personnel Database application was developed to make it easier for employees and staff of the Faculty of Education, State University of Surabaya to carry out their duties, both teaching and educational staff. Based on the explanation above, this research was conducted to determine the effectiveness of the